HISTORY OF THE FOURTH CENTURY CHURCH COUNCIL AND ITS RELATIONSHIP TO GMIM: SEJARAH KONSILI GEREJA ABAD EMPAT DAN RELAVANSINYA BAGI GMIM - Evi Stans Evlin Tumiwa; Elsa Marsela Kaparang (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the History of the Fourth Century Church Council and its Relevance for GMIM. The research method used is a qualitative method with a historical approach. The aim of this research is so that congregations can learn about the history of the fourth century church council and its relevance for GMIM. It is hoped that the results of the research will provide the congregation with an understanding and knowledge of the history of the fourth century church council and its relevance for GMIM. To be able to grow, develop and learn from history and become a congregation that continues to be a blessing. The conclusion obtained is that the GMIM, which is a member of the church, must continue to be updated and reformed so that it can understand the church council of the fourth century and can be a lesson for the church today.